2013
DOI: 10.1002/ajim.22274
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and work‐related musculoskeletal symptoms among intensive care unit nurses: a comparison between job demand‐control and effort‐reward imbalance models

Abstract: The ERI model appears to capture the magnitude of the musculoskeletal health risk among nurses associated with job stress at least as well and possibly better than the JDC model. Our findings suggest that combining the two models provides little gain compared to using effort-reward imbalance only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
1
45
0
1
Order By: Relevance
“…A recent study comparing the demand-control model and the effort ERI found a greater association between ERI and the musculoskeletal problems. 83 The authors concluded that using both models in a musculoskeletal context provides little added value and suggested using the ERI. 83 Our results support this conclusion in a psychological distress context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study comparing the demand-control model and the effort ERI found a greater association between ERI and the musculoskeletal problems. 83 The authors concluded that using both models in a musculoskeletal context provides little added value and suggested using the ERI. 83 Our results support this conclusion in a psychological distress context.…”
Section: Discussionmentioning
confidence: 99%
“…83 The authors concluded that using both models in a musculoskeletal context provides little added value and suggested using the ERI. 83 Our results support this conclusion in a psychological distress context.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that relations of PSFs and physical exhaustion have likely increased the risk of MSDs in nurses. High perceived workload, role conflicts, low job satisfaction, poor social support, time pressure, low justice and respect in the workplace were among those factors constantly effected these disorders in several studies [7,21,[30][31][32][33].…”
Section: Psychological Factorsmentioning
confidence: 98%
“…Lower back disorders were the most common problem in many studies [14,33,41,42]. Lower back and neck are body areas most frequently affected by pain [28].…”
Section: Musculoskeletal Symptoms Prevalencementioning
confidence: 99%
“…The Intensive Care Unit (ICU) is considered to be a stressful work environment for nurses, since a growing body of evidence suggests several work-related stress sources (1,2) . Prolonged work-related stress has been linked with psychological disturbances that affect nurses' physical and mental health status (1,3) , along with altered professional performance, mediated through emotional exhaustion, vicarious trauma, fatigue, and professional burnout (4,5) .…”
Section: Introductionmentioning
confidence: 99%